Study of separation force in constrained surface projection stereolithography. Issue 2 (20th March 2017) - Pan, Yayue; He, Haiyang; Xu, Jie; Feinerman, Alan
Abstract : Purpose: Recently, the constrained surface projection stereolithography (SL) technology is gaining wider attention and has been widely used in the 3D printing industry. In constrained surface projection SL systems, the separation of a newly cured layer from the constrained surface is a historical technical barrier. It greatly limits printable size, process reliability and print speed. Moreover, over-large separation force leads to adhesion failures in manufacturing processes, causing broken constrained surface and part defects. Against this background, this paper investigates the formation of separation forces and various factors that affect the separation process in constrained surface projection SL systems. Design/methodology/approach: A bottom-up projection SL testbed, integrated with an in-situ separation force measurement unit, is developed for experimental study. Separation forces under various manufacturing process settings and constrained surface conditions are measured in situ . Additionally, physical models are constructed by considering the liquid resin filling process. Experiments are conducted to investigate influences of manufacturing process settings, constrained surface condition and print geometry on separation forces. Findings: Separation forces increase linearly with the separation speed. The deformation and the oxygen inhibition layer near the constrained surface greatly reduce separation forces. The printing area, area/perimeter ratio and the degree of porousness of print geometries have a combined effect on determining separation forces. Originality/value: This paper studied factors that influence separation force in constrained surface SL processes. Constrained surface conditions including oxygen inhibition layer thickness, deformation and oxygen permeation capability were investigated, and their influences on separation forces were revealed. Moreover, geometric factors of printing layers that are significant on determining separation forces have been identified and quantified. This study on separation forces provides a solid base for future work on adaptive control of constrained surface projection SL processes.